1994
DOI: 10.1007/bf00014443
|View full text |Cite
|
Sign up to set email alerts
|

The tRNASer-isoacceptors and their genes in Nicotiana rustica: genome organization, expression in vitro and sequence analyses

Abstract: The existence of six serine codons results in a complex pattern of tRNA(Ser) isoacceptors in organisms and organelles. According to the original wobble hypothesis, a minimum of three isoacceptors should be sufficient to read the six serine codons. We have isolated five cytoplasmic tRNAs(Ser) from leaves of Nicotiana rustica. Their nucleotide sequences identify them as four different isoacceptors with the anticodons cm5UGA, CGA, IGA and GCU. For tRNA(Ser) with IGA anticodon, two species have been detected which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…An intact pre-tRNA tertiary structure is required for clevage by wheat germ RNase P. A number of nuclear plant tRNA gene variants have been described which are defective in maturation of their transcripts when assayed in an unfractionated wheat germ processing system (Stange et al, 1991;Fuchs et al, 1992;Teichmann et al, 1994). We have used some of these naturally occurring mutants to determine the influence of the implied structural alterations in the corresponding pre-tRNAs on cleavage by purified wheat nuclear RNase P. Tn contrast to the Escherichiu coli enzyme, which recognizes a variety of substrates diverging from the canonical tRNA structure Guerrier-Takada et al, 1988;Forster and Altman, 1990), the wheat enzyme is very sensitive against structural aberrations: changes involving the T-stem and T-loop domain, and even the presence of an intron in the anticodon loop, significantly reduce the cleavage efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An intact pre-tRNA tertiary structure is required for clevage by wheat germ RNase P. A number of nuclear plant tRNA gene variants have been described which are defective in maturation of their transcripts when assayed in an unfractionated wheat germ processing system (Stange et al, 1991;Fuchs et al, 1992;Teichmann et al, 1994). We have used some of these naturally occurring mutants to determine the influence of the implied structural alterations in the corresponding pre-tRNAs on cleavage by purified wheat nuclear RNase P. Tn contrast to the Escherichiu coli enzyme, which recognizes a variety of substrates diverging from the canonical tRNA structure Guerrier-Takada et al, 1988;Forster and Altman, 1990), the wheat enzyme is very sensitive against structural aberrations: changes involving the T-stem and T-loop domain, and even the presence of an intron in the anticodon loop, significantly reduce the cleavage efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Stange and Beier, 1987). Similarly, although investigation of a variety of pre-tRNAs indicated that mutations disrupting the tRNA structure severely impair overall processing in this plant in vitro system (Stange et al, 1991 ;Fuchs et al, 1992;Teichmann et al, 1994), it is not clear at present which of the enzymes involved is most sensitive to these changes. To approach these questions, and to gain insight into the molecular composition and substrate requirements of nuclear RNase P from higher as percentage product formation.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Plasmids pAtSl, pAtS5 and pAtS6 coding for functional (pAtS6) and nonfunctional (pAtS 1 and pAtS5) Arubidopsis thalianck pre-tRNAs"' have been described by Bcier and Beier (1992). Plasmids pNtS3, pNtS4, pNtS5 and pNtS7 coding for functional (pNtS3, pNtS5 and pNtS7) and non-functional (pNtS4) Nicotiana rusticu pretRNAs'" have been described by Teichmann et al (1994). Plasmid pPMS coding for an intron-containing functional pretRNA"" from S. cerevisiue has been described by Olson et al (1981).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that most plant tRNA genes are efficiently transcribed in both extracts [13,25,28]. Here we have performed in vitro transcription of pTtY4 to pTtY9 in HeLa cell nuclear extract at 1 mM Mg 2+ concentration.…”
Section: In Vitro Transcription Of Triticum Trna Tyr Genes In Helamentioning
confidence: 99%